Cultivating educational adaptability through collaborative transdisciplinary learning spaces - Aishwarya Ramachandran; Meg Schwellnus; Derek Gladwin; Ryan Derby-Talbot; Naoko Ellis (Springer, 2024)
Abstract Empowering students and scholars to effectively address complex societal challenges frequently entails embracing unconventional pathways to foster transdisciplinary (TD) education. This empowerment is further facilitated by collaborative efforts supported by the TD experience. This paper examines one such initiative: a student-centered, experimental design of a TD doctoral pilot program for environmental sustainability at the University of British Columbia, a large, research-intensive public university in Canada. In this study, we documented shifts in participants' development and assessed the impact of TD collaboration conditions on the educational design process. The findings indicate that engaging in collaborative TD experiences yields substantial pedagogical benefits, introducing novel opportunities for design and experimentation. This TD space appears to offer conducive conditions for students and faculty to more effectively navigate adaptive and innovative contexts within higher education. Pedagogical experimentation of this nature provides insights that are challenging to derive from theoretical speculation alone, offering potential pathways for today's learners and educators as they confront complex societal challenges.